Social Support as a Predictor of Positive Peer Relationships in Boarding School Students - Alfa Muntadhar; Yulia Ayriza; Fakhri Yacob (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Learning in a boarding school environment presents unique challenges due to academic demands and responsibilities that may influence the quality of peer relationships. This condition raises questions regarding the extent to which social support contributes to the development of positive peer relationships. This study aims to examine the effect of social support on positive peer relationships among boarding school students. This study employed a quantitative approach using a survey design. The research instruments consisted of psychological scales that had undergone content and construct validity testing, as well as reliability testing using Cronbach’s Alpha. Data were collected through questionnaires distributed to respondents and subsequently analyzed using SmartPLS 3 through the PLS algorithm, bootstrapping, and PLSPredict procedures. The results indicate that social support plays a significant role in predicting positive peer relationships, with an effective contribution of 21.1%. Social support also significantly influences the dimensions of intimacy, popularity, trust, and insight within peer relationships. These findings highlight the importance of social support in strengthening peer relations within the boarding school environment. Theoretically, this study contributes to a deeper understanding of social factors in the development of peer relationships, while practically it provides a basis for developing mentoring programs aimed at improving the quality of student interactions.